A guide to intra-state wars : an examination of civil, regional, and intercommunal wars, 1816-2014 /: an examination of civil, regional, and intercommunal wars, 1816-2014. ([2016]) - Dixon, Jeffrey C; Sarkees, Meredith Reid, 1950-
No abstract available